(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2012)
Bioactive compounds such as vitamins, antioxidants, essential oils, enzymes, beneficial microorganisms, etc. can be preserved using various encapsulation techniques. These techniques aim to maintain their activity by completely or partially isolating them from the environment until they are released at the appropriate time and place. Encapsulation is also a source of new ingredients with unique properties. It allows aromas and flavors to be masked or preserved, reduces agglomeration problems and liquid volatility, and improves additive dosage and, therefore, cost-effectiveness. Methods that use sodium or potassium alginate as a precursor to the encapsulating matrix are coacervation and ionic gelation. Combining both mechanisms, our laboratory has studied the encapsulation of yerba mate (Ilex paraguariensis) extracts in calcium alginate matrices with and without chitosan coating to preserve their antioxidant properties. Complex systems have been developed with the addition of filler (starch granules). This allowed to increase the efficiency of the active compound content and the modulation of its release in a simulated gastro-intestinal system.